CARACTERÍSTICAS DE CUARZOS - Fernández, B; Fernández, A.; Rodríguez, M. (Tecnociencia, 2003)
Dating of panamanian archaeological ceramics, by the fine grain technic, exhibited significant differences vis a vis the european ones, as to sensitivity radiation. A sistematic program was initiated with the objective of determining the source of such differences. As part of this program, the first task undertaken was designed to characterize quartz as the main thermo-luminiscent item among ceramics. Two extreme representavive where chosen. One of them of advance geological age, of low cristalization and quite affected by atmospheric impact and other one of recent geological age, well cristalized, of little exposure to atmospheric impact. The results of EMS in the case of european quartz grains, exhibited more wear at the edges and uneveness in the surface. All the samples when DTA is applied show the characteristic transition from structure alpha to beta. Also DTA indicates more cristalinity in the panamenian quartz than in the european quartz. DTA and EMT show an european quartz very fragmented in its interior. Furthermore, EMT indicated lots of dislocations, fissures, macles and quite a number of water bubbles in the european quartz, which are related to the presence of H4O4 thermoluminiscent sites. The panamanian quartz only exhibited the water bubbles, and in a vary small number, when heated to 700°C.